Smoke in mirrors - Krentz, Jayne Ann (G.P. Putnam's Sons, 2002)
Charming, seductive scam artist Meredith is dead, and the job of proving that death was no accident is left to Leonora Hutton, who has always been there when Meredith needed her. Thomas Walker has something to prove about Meredith, too -- that the million-dollar inheritance she left Leonora was embezzled from a college endowment fund entrusted to his brother. He gives Leonora two choices: Turn the money over to him or be named an accomplice to Meredith's crime. Leonora makes the blackmail mutual. To gain her cooperation, Thomas must help her investigate Meredith's death, which shows some uncanny similarities to the supposed suicide of Thomas's brother's wife, who had also worked in the campus building known as Mirror House. Their first clue is a folder of clippings about an unsolved murder in Mirror House 30 years ago, so academic librarian Leonora secures a job cataloging the building's vast collection of antique mirrors and books about them, to search for reflections of that past case in their present situation. Smoke in Mirrors tells of a looking-glass world, where academic jealousy, murderous rage, and deadly passion are superimposed, and nothing is as it seems.